Prevalence and clinical characteristics of metabolic syndrome among Malaysian hypertensive subjects using the international diabetes federation definition - Azizi A.; Rafidah H.M. (International Islamic University Malaysia, 2024)
Individuals with metabolic syndrome are at increased risk for developing cardiovascular disease and diabetes mellitus. This study was carried out to determine the prevalence of metabolic syndrome and clinical characteristics in hypertensive patients according to the criteria of the new International Diabetes Federation (IDF) definition. Hypertensive patients were recruited from the Medical Out-Patient Department, Kuantan Hospital. The five components of metabolic syndrome were examined which included blood pressure (? 130/85 mmHg), fasting glucose (? 5.6mmol/L), fasting triglycerides (? 1.7 mmol/L), high-density lipoprotein (HDL) cholesterol level (< 1.03mmol/L in males and < 1.29mmol/L in females), and abdominal obesity (waist circumference: men > 90cm; women > 80cm). Out of 139 hypertensive patients, there were 113 met all the selection criteria consisted of 61 male and 52 female subjects. The participants' age ranged from 21 to 91 years (51.916.8 years; meanSD), and body mass index 13.5-42.3 kg/m2 (27.54.9 kg/m2). According to the IDF criteria, the prevalence of central obesity was 67.2% in men and 84.6% in women. Among the 113 hypertensive subjects over 21 years of age, 51 subjects or 45.1% had metabolic syndrome. The present data revealed that there was high prevalence of metabolic syndrome in Malaysian hypertensive subjects. This finding was supported by the fact of high prevalence of central obesity among the study subjects.